The Grammatical Errors Encountered in Spoken English of Indonesian Ex Singapore Female Laborers - . Erik (Magister Scientiae, 2009)
The language mostly used by the subjects when they worked in Singapore is English. However, the writer found that many subjects of the study under report were still influenced by their mother tongue, in this case Bahasa Indonesia, and also by their employer in the past. This condition made those subjects often produce wrong sentences. The situations above motivated the writer to conduct a study on analyzing the subjects’ errors in spoken English. In gaining the data, the writer used a small tape recorder to record all the interviews spontaneously answered by the subjects, a note book to write down the subjects’ data completely and also a camera to take a picture of the interviewing process. After analyzing the data, the prediction of the causes of errors were not only because of the mother tongue influence or because of the employer’s influence in the past but also because of the reflection of general characteristics of rule learning such as incomplete application of rules, and failure to learn conditions under which rules applied as well.